2020
DOI: 10.1002/mma.6501
|View full text |Cite
|
Sign up to set email alerts
|

A new regular infinite matrix defined by Jordan totient function and its matrix domain in p

Abstract: In this paper, we first define a new regular matrix by using the arithmetic function called Jordan totient function and study the matrix domain of this newly introduced matrix in the Banach space ℓp. After computing the dual spaces of this new space, we characterize certain matrix mappings related to this space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Recently, several authors constructed interesting Banach sequence spaces using the domain of special triangles, for instance İlkhan [26], İlkhan and Kara [24], Roopaei [54,55], Roopaei et al [53], and Yaying et al [64]. We followed this approach and introduced BK spaces k (F(B)) and ∞ (F(B)) defined as the domain of the product matrix F (B(x, y, z)) in the spaces k and ∞ , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several authors constructed interesting Banach sequence spaces using the domain of special triangles, for instance İlkhan [26], İlkhan and Kara [24], Roopaei [54,55], Roopaei et al [53], and Yaying et al [64]. We followed this approach and introduced BK spaces k (F(B)) and ∞ (F(B)) defined as the domain of the product matrix F (B(x, y, z)) in the spaces k and ∞ , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The set X is a sequence space and is known as the domain of matrix in the space X. Additionally, if X is BK -space and is a triangle, then X is also BK -space endowed with the norm s X = s X [27], where the matrix = (ψ rv ) is called a triangle if ψ rr = 0 for all r ∈ N and ψ rv = 0 for v > r. Using this famous result several authors [4,29,35,41,48] in the literature constructed new BK -spaces. We also mention [22,23,26,[53][54][55][62][63][64] for some recent publications and textbooks [6,47,61] in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Schoenberg 23 showed that this special mapping is regular. In İlkhan et al, 21 the authors showed that the Jordan totient matrix operator is also regular.…”
Section: Some New Banach Spaces Derived By Jordan's Functionmentioning
confidence: 99%
“…The Jordan totient matrix operator normalΥr=false(υnkrfalse) is defined by İlkhan et al 21 as υnkr=Jrfalse(kfalse)nr,if3.0235ptkfalse|n0,if.5emkn for each r.…”
Section: Some New Banach Spaces Derived By Jordan's Functionmentioning
confidence: 99%
See 1 more Smart Citation